Implemetasi Evidence Based Nursing: Efek Mobilsasi Dini pada Peningkatan Fungsi Fisik pada Pasien Paska Bedah Jantung (CABG) - Sugiyono, Sugiyono; Irawati, Diana; Natashia, Dhea (Journal of Telenursing (JOTING), 2022)
This study aims to apply the effect of early mobilization on improving physical function in patients after CABG cardiac surgery based on the latest research results (Evidence-Based Nursing Practice). The method used was an experiment through the application of intervention for five days and continued with measurements on day 6 in the intervention group before the patient was sent home with the target being able to run (6'WMT). The research results show that the application of EBPN obtains a p-value of 0.005. In conclusion, there is a relationship between giving early mobilization interventions and functional ability with the 6 MWT test. Keywords: Evidence-Based Nursing, Physical Ability (6'WMT), Early Mobilization, Post Cardiac Surgery (CABG)